The relationship between perceived training opportunities, intrinsic motivation and task performance among support staffat Institute of Teacher Education Tun Abdul Razak Campus (IPGKTA) Kota Samarahan/ Mohamad Zainuddin Mohd Said - Mohd Said, Mohamad Zainuddin (2018)
This empirical study is accomplished to predict Task Performance in relation to Perceived Training Opportunity and Intrinsic Motivation. The sample consists of 95 respondents in Institute of Teacher Education Tun Abdul Razak Campus (IPGKTA), Kota Samarahan. This was accomplished through quantitative method of data collection namely questionnaire. The finding of study revealed that Perceived Training Opportunity and Task Performance are important to increase employee’s performance. Pearson Correlation and regression analysis was carried out for the collected data. The correlation analysis shows that Perceived Training Opportunity has relationship and significant relationship toward Task Performance. Meanwhile, Intrinsic Motivation show low relationship and insignificant relationship toward Task Performance. This finding indicated that it is recommends for future studies to further investigate regard this study in other organization.